A Note on Bankruptcy Rules and Credit Constraints in Temporary Equilibrium - Eichberger, Jurgen (Econometrica, 1989)
In this note it is argued that bankruptcy rules and credit constraints are intrinsically related concepts. Bankruptcy occurs because credit is constrained. By introducing the concept of a «consistent» credit rationing scheme, it can be shown that a temporary equilibrium exists if credit rationing is consistent and if lenders have more conservative expectations with regard to the borrower's future repayment capability than the borrower